2023
DOI: 10.1029/2022jd038238
|View full text |Cite
|
Sign up to set email alerts
|

Responses of the AC/DC Global Electric Circuit to Volcanic Electrical Activity in the Hunga Tonga‐Hunga Ha'apai Eruption on 15 January 2022

Abstract: Responses of the AC and DC global electric circuits (GECs) to the large eruption of the Hunga Tonga‐Hunga Ha'apai (HT‐HH) volcano on 15 January 2022 are discussed. The AC‐related investigation is based on Schumann resonance (SR) measurements from six stations on four continents. The DC‐related investigation utilizes atmospheric electric field (potential gradient, PG) measurements from six recording stations in Europe and the USA. According to data from the GLD360 and WWLLN lightning detection networks, the pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 141 publications
0
3
0
Order By: Relevance
“…To illustrate the range of possibilities of the proposed ELF signal azimuth analysis applied to the ELA11 receiver measurements we selected the day of 15 January 2022 (0–24 hr UT). We processed the data to extract information on natural ELF wave fields anisotropies and additionally, to check constraints on revealing the ELF signature associated with the HT volcano eruption (Bor et al., 2023; Nickolaenko et al., 2022). The eruption signatures in the time range 4:15–15:50 UT for the main eruption and in the time range 8:35–9:30 UT for the next weaker one, are visible in our data, as presented in the 24‐hr dynamic spectrum evolution at Figure 2.…”
Section: Azimuths Of Elf Electromagnetic Waves Registered In the Hyla...mentioning
confidence: 99%
See 1 more Smart Citation
“…To illustrate the range of possibilities of the proposed ELF signal azimuth analysis applied to the ELA11 receiver measurements we selected the day of 15 January 2022 (0–24 hr UT). We processed the data to extract information on natural ELF wave fields anisotropies and additionally, to check constraints on revealing the ELF signature associated with the HT volcano eruption (Bor et al., 2023; Nickolaenko et al., 2022). The eruption signatures in the time range 4:15–15:50 UT for the main eruption and in the time range 8:35–9:30 UT for the next weaker one, are visible in our data, as presented in the 24‐hr dynamic spectrum evolution at Figure 2.…”
Section: Azimuths Of Elf Electromagnetic Waves Registered In the Hyla...mentioning
confidence: 99%
“…As described in more detail below, the novelty of the present approach is the use of a difference technique that intrinsically introduces selective temporal filtering that can be used to remove power line interference or target specific temporal signatures. Thus a significant amount of the measurement data can be applied for the azimuth determinations, contrary to previous studies focusing on large ELF impulses in the data (see, e.g., a recent description in Nickolaenko et al, 2023) For illustration of the possibilities of the proposed novel approach, we analyze observations from the day of 15 January 2022, when occurrence of the Hunga Tonga (HT) volcano eruption created a strong compact ELF source Mezentsev et al, 2022;Bor et al, 2023; see also Nickolaenko et al, 2023). We also present the capabilities of single site monitoring of global thunderstorm activity.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneous observation of SR anomalies in France, Italy, Russia, and Japan were reported during the 2022 Tonga eruption, where localized lightning field sources were formed by aggregation in the eruption cloud [32]. J. Bor et al [33] used the data observed by multiple SR and PG (potential gradient) measurement stations distributed globally to study the GEC's response to the eruption of the Tonga volcano. SR and PG intensities were used to describe the AC (alternating current) and DC (direct current) components of the GEC, respectively.…”
Section: Introductionmentioning
confidence: 99%